Improving the desorption efficiency of styrene based on inorganic inhibitor modified activated carbon - LIANG Dingcheng; SU Xuechao; XIE Qiang; ZHANG Lianxiu; DENG Qingwen; ZHOU Hongyang; LIU Jinchang (矿业科学学报)
When activated carbons containing carbon-carbon double bond reactive VOCs such as saturated styrene are thermally desorbed, it is easy to form macromolecular polymers at high temperatures to block the pores of activated carbon and reduce the adsorption performance of activated carbon. This study therefore proposes to use the impregnation method to load the inorganic inhibitor on the activated carbon for modification. Specifically, we investigated the effect of inorganic polymerization inhibitor type, concentration and desorption temperature on the adsorption, desorption and regeneration properties of styrene and probed into the inhibition mechanism via gas adsorption method, X-ray photoelectron spectroscopy and scanning electron microscopy. Results show that when 0.05 mol/L FeCl3 was loaded as an inhibitor on the columnar activated carbon by impregnation, the activated carbon demonstrated maximum desorption effect at 100 ℃. The impregnation method enabled FeCl3 to be effectively loaded on activated carbon, the free radicals quenched at high temperature and the polymerization of styrene was inhibited to some extent. This method may effectively alleviate the difficulty of desorption and regeneration when activated carbon adsorbs and purifies reactive VOCs.